The Influence of Internal and External Factors on Non-Performing Financing at Islamic Commercial Banks in 2018-2022 - Putri Novia Rahmawati; Gita Syafira Setiady; Mardi Mardi; Itah Miftahul Ulum (Publikasi Indonesia, 2024)
Financing is one of the main functions in Islamic banking, the risk that can occur in such financing is non-performing financing or Non-Performing Financing (NPF). This study aims to determine the factors that affect the NPF of Islamic commercial banks in the period 2018-2022, the variables used in this study are Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Inflation, and Gross Domestic Product (GDP), this study uses a quantitative approach, using panel data regression analysis with the Generalized Least Square (GLS) estimation method. Partially, the CAR variable has a positive effect on NPF, the FDR variable has a negative effect on NPF, while the Inflation and GDP variables have no effect on NPF